The architect versus the citizenry: what is the role of participation in architecture? - Dreifuss-Serrano, Cristina (2023)
Participatory architecture has become increasingly present both in the discourse and in the architectural practice of the last two decades. It is important to question to what extent participation is real, and if the complete practice of it, as a free exercise of citizenship within the design processes, does not contradict the practices of architecture. Through theoretical reflection resulting from the observation of examples, risks and lessons of participatory processes are proposed, both for teaching and for the practice of architecture in the contemporary context.